2014
DOI: 10.1038/jcbfm.2014.193
|View full text |Cite
|
Sign up to set email alerts
|

CpG Preconditioning Regulates Mirna Expression That Modulates Genomic Reprogramming Associated with Neuroprotection against Ischemic Injury

Abstract: Cytosine-phosphate-guanine (CpG) preconditioning reprograms the genomic response to stroke to protect the brain against ischemic injury. The mechanisms underlying genomic reprogramming are incompletely understood. MicroRNAs (miRNAs) regulate gene expression; however, their role in modulating gene responses produced by CpG preconditioning is unknown. We evaluated brain miRNA expression in response to CpG preconditioning before and after stroke using microarray. Importantly, we have data from previous gene micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[8] We believe that finding microRNA that is altered by the rupture of aneurysms could more simply explain the complex mechanism of EBI because each miRNA has many potential mRNA targets; thus, a broad spectrum of gene expression could be affected by the presence or absence of an individual miRNA. [20] e current study also has certain limitations. e number of patients included in the current study was relatively small.…”
Section: Discussionmentioning
confidence: 86%
“…[8] We believe that finding microRNA that is altered by the rupture of aneurysms could more simply explain the complex mechanism of EBI because each miRNA has many potential mRNA targets; thus, a broad spectrum of gene expression could be affected by the presence or absence of an individual miRNA. [20] e current study also has certain limitations. e number of patients included in the current study was relatively small.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have indicated that electroacupuncture, fastigial nucleus stimulation, and vagus nerve stimulation promote neuroprotection through induction of the microRNA in cerebral ischemic animal models, respectively [79][80][81] . Some molecules, such as cytosine-phosphate-guanine, insulin-like growth factor-1, natural vitamin E a-tocotrienol, and lithium induce neuroprotection in cerebral ischemia by regulating some specific miRNAs [82][83][84][85] .…”
Section: Functions and Molecular Mechanisms Of Ncrnas In Cerebral Iscmentioning
confidence: 99%
“…CpG preconditioning after stroke showed that large numbers of miRNAs are regulated within 24 hours. However, a unique set of miRNAs was suppressed that are associated with upregulation of several neuroprotective genes in CpG‐preconditioned mice, compared to saline‐treated mice, after stroke, implying that upregulation of miRNAs can play a role in neuroprotection by genomic reprogramming …”
Section: Neuroprotective Role Of Ncrnasmentioning
confidence: 99%